Comparative Analysis of Jumping and Landing Velocity of the Young Elite Spikers of the Iranian National Volleyball Team While Performing Block Jump - Ali Fatahi; Razieh Yousefian Molla; Mitra Ameli (Biyumikānīk-i varzishī)
Objective: Accurate velocity analysis is essential when performing the block jumping technique on the net by various spikers because it will improve this performance and prevent injury. This study aimed to compare the jump and landing velocity of the Iranian national team’s young elite spikers when performing block jump skills. Methods: A total of 21 young elite male volleyball players of the Islamic Republic of Iran (11 wing spikers and 10 middle spikers) participated in the present study. Subjects performed block jumping skills. Force data in the X, Y, and Z directions were obtained directly from the force plate’s output. Then, the area under the force-time curve was calculated as an impulse. The rate of changes in mean, maximum, and minimum velocities and the resultant in each direction (X, Y, and Z) were obtained by dividing every subjects’ impulse data in each direction to his mass. Descriptive statistics, the Shapiro-Wilk test (checking the normality of data distribution), and independent t-test were used to analyze and compare the two groups’ variables (P≤0.05). Results: The difference between the mean velocities on the X and Z planes and the mean rates between the two groups was significant. The other velocity variables in the two groups were not significant (P˂0.05). Conclusion: The results of the present study can help coaches, players, and volleyball professionals to pay more attention to the velocity of execution during block jump technique, especially between middle and wing spikers in different directions during the match and design of the training program.